Traumatic stress : from theory to practice - Freedy, John R.; Hobfoll, Stevan E. (New York : Plenum Press, 1995)
(from the preface) Even a passing interest in daily news events confirms that violent crime, disasters, serious accidents, war, and other forms of traumatic events occur frequently and with great impact upon individuals, families, and communities. On a more scientific note, extant research studies have confirmed several crucial facts regarding the nature of traumatic events. These facts include: (1) that traumatic events occur frequently, impacting large numbers of people; (2) that exposure to traumatic events substantially increases the risk of several serious mental health problems; and (3) that it is possible to limit the impact of traumatic events through the application of prevention, assessment, and treatment strategies. This volume translates extant scientific knowledge concerning traumatic events and mental health into state-of-the-art prevention, assessment, and treatment activities for mental health professionals among whom intervention is their daily bread.
This volume is intended to further inform mental health practitioners regarding: (1) the high prevalence of traumatic events; (2) the types of psychosocial problems associated with traumatic events; and (3) prevention, assessment, and treatment (psychosocial and biological) strategies available to alleviate trauma-engendered suffering.
[The authors] have designed the book to be a clinical handbook for mental health professionals. . . . In particular, the following practitioners may find the information in this volume of considerable utility: psychologists, psychiatrists, social workers, psychiatric nurses, or mental health counselors from related fields. It can be of use both to licensed practitioners as well as students in these various mental health fields.
Traumatic stress: A blueprint for the future, John R. Freedy and Stevan E. Hobfoll
Keywords: traumatski stres